Hybrid coastal edges in the Neuquén Basin (Allen Formation, Upper Cretaceous, Argentina) - Armas, María Paula (2015)
The Allen Formation records the first Ingression Atlantic to the Neuquén Basin during the Late Cretaceous. The definition of lithofacies and facies associations interpretation for stratigraphic sections in Paso Córdoba and Salitral Moreno area, Río Negro, Argentina allowed to establish the depositional system that characterized this transgression in the northeastern edge of the Basin. In this paper we present sedimentological analysis of conglomeratic, sandstone, heterolithic and pelitic facies, which allowed the interpretation of tidal channels (CM), intertidal flats (PI), tidal flat influenced by storms (PT), subtidal flat (PS) and shoreface deposits (CP) parts of the depositional environment. These deposits represent a sedimentary records preserved example of hybrid systems, in which, the base of the sequence has greater tidal influence, while the upper portion is dominated by wave action. The paleocurrent data indicating a NNW-SSE direction to the shore and correlations and spatial distribution of facies associations propose paleogeographic and paleoenvironmental interpretations to Malargüe Group base. Then in this paper the relationship of this coastal environment presents with wind systems previously defined in this area for the Allen Formation.